Do passive houses need passive people? Evaluating the active occupancy of Passivhaus homes in the United Kingdom. (June 2020) - Zhao, Jing; Carter, Kate
Abstract: The Passivhaus model emphasises a high standard of building fabric insulation and controlled ventilation with heat recovery in order to achieve comfort and reduce energy use. The implication is that environmental control is achieved by the building fabric and ventilation system with little need for significant occupant interaction or behaviour change in order to achieve comfort and energy efficiency. This paper challenges such views with new research that draws upon empirical data from case studies of houses in the UK built to the Passivhaus standard. It uses inductive analysis of interview data, documenting user-interactions with the houses, and opinions and attitudes of the occupants towards living in a Passivhaus. The research includes both social rented housing and private ownership tenures. The results of this study show both comfort-driven and energy saving-driven behavioural adaptations amongst the occupants and that the Passivhaus system demands a high level of occupant interaction in order to achieve both comfort and energy efficiency. 'Designing out' occupant's behaviour and reinforcing the image of automated comfort without facilitating occupant behavioural adaptations, could lead to user dissatisfaction in Passivhaus buildings.